Corrugating defect/remedy manual. (TAPPI Press, 2018)
This manual provides a basis for common knowledge of terms, definitions, and methods of correction of corrugated operational defects. The manual illustrates and provides causes and remedies for hundreds of defects affecting corrugated boxes. The manual is divided into four parts: Corrugated Problems; Printing Problems; Die Cutting Problems; and Finishing and Manufacturers' Joint Problems.
"TAPPI PRESS Item Number: 0101R153"
Keywords: Corrugated paperboard -- Defects.; Corrugated paperboard -- Defects -- Terminology.; elektronické knihy; electronic books